Peran Supervisi Akademik dalam Meningkatkan Kompetensi Guru di Madrasah Aliyah - Nana Suciana; Revina Revina; Nureehan Mapa; Saba’a Hasan Mohammed Al-Fakih; Lina Herlina; Ridwan Haris (STIT Fatahillah, 2026)
Academic supervision is a crucial strategy for improving the quality of education, particularly in developing teacher competency in Islamic Senior High Schools (Madrasah Aliyah). As the primary implementers of the learning process, teachers are required to possess strong pedagogical, professional, social, and personal competencies to create effective and high-quality learning. However, in practice, various obstacles remain, such as low learning innovation, suboptimal use of educational technology, and weak classroom management. This paper aims to analyze the role of academic supervision in improving teacher competence in Madrasah Aliyah (Islamic Senior High School). The method used is library research, reviewing various sources such as books, scientific journals, and educational regulations relevant to academic supervision and teacher competence. The results of the study indicate that academic supervision plays a significant role in helping teachers improve the quality of lesson planning, learning implementation, the use of educational media and technology, and learning evaluation. Furthermore, academic supervision can also improve teacher motivation, discipline, and professionalism through continuous and humanistic development. Effective academic supervision requires the principal's competence as a supervisor, a harmonious working relationship, and follow-up on supervision results. With planned and continuous academic supervision, teacher competencycan develop optimally, thus improving the quality of learning and education at Islamic Senior High Schools.